2023
DOI: 10.31223/x5nm1w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent effect of El Niño on global economic growth

Abstract: El Niño-Southern Oscillation (ENSO) shapes extreme weather globally, causing myriad socioeconomic impacts. But whether economies recover from ENSO events and how changes to ENSO from anthropogenic forcing will affect the global economy are unknown. Here we show that El Niño persistently reduces country-level economic growth, attributing $4.9T and $7.4T in global income losses to the 1982-83 and 1997-98 El Niños, respectively. Increases in ENSO amplitude and teleconnections from warming cause $374T in discounte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Numerous studies investigating the effects of El Niño have shown that it has a profound impact on regional climates and ecosystems, extending well beyond its primary area of influence. These widespread impacts include various aspects such as disease incidence 14 , susceptibility to mass coral bleaching 15 , changes in fire 16 , in fish abundance and distribution 17 , and even its effects on national economies, sectors, and food security 18,19 . Because 600 million people live in coastal areas less than 10 meters above sea level, the links between ENSO and coastal vulnerability have been studied extensively [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: One Of El Niño's Footprints: Reshaping and Flooding The Worl...mentioning
confidence: 99%
“…Numerous studies investigating the effects of El Niño have shown that it has a profound impact on regional climates and ecosystems, extending well beyond its primary area of influence. These widespread impacts include various aspects such as disease incidence 14 , susceptibility to mass coral bleaching 15 , changes in fire 16 , in fish abundance and distribution 17 , and even its effects on national economies, sectors, and food security 18,19 . Because 600 million people live in coastal areas less than 10 meters above sea level, the links between ENSO and coastal vulnerability have been studied extensively [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: One Of El Niño's Footprints: Reshaping and Flooding The Worl...mentioning
confidence: 99%
“…The El Niño‐Southern Oscillation (ENSO) cycle is the most extreme interannual climate fluctuation on Earth, with irregular warm El Niño and cold La Niña phases (Timmermann et al., 2018). Such variations in ENSO system could ripple via atmospheric teleconnection, resulting in unusual weather and climate events around the world (Ropelewski & Halpert, 1987; Steiger et al., 2021) as well as societal and economic losses subsequently (Callahan & Mankin, 2023; Hsiang et al., 2011). Due to the profound influence of ENSO on the global weather and socio‐economy, accurate prediction of ENSO as far in advance as possible has long been an ambition of climate science.…”
Section: Introductionmentioning
confidence: 99%
“…The El Niño‐Southern Oscillation (ENSO) has a large influence on global weather, leading to significant human impacts, ranging from economic (Callahan & Mankin, 2023) and agricultural (Iizumi et al., 2014) to emergency management (Guimarães Nobre et al., 2019). Accurate forecasting of ENSO events provides a vital warning for these sectors, meaning any improvements to the forecast could have an appreciable human benefit.…”
Section: Introductionmentioning
confidence: 99%